(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The Electricity crisis in Lebanon represents one of the most severe structural challenges in the Middle East, extending beyond the mere fulfillment of citizens’ energy needs to impact various economic and public service sectors. This deterioration has disrupted the functionality of essential public utilities and heightened consumer grievances, as the Lebanese Electricity Corporation (Électricité du Liban) is mandated to ensure the continuity and sustainability of electricity provision as a fundamental public service. The sector suffers from significant administrative and structural deficiencies, primarily stemming from weak implementation of good governance principles, including transparency, accountability, and managerial efficiency, which are essential to maintaining the viability of public utilities. The problem is further compounded by legislative gaps and a lack of comprehensive legal and institutional reforms amid Lebanon’s ongoing economic and financial crisis. Moreover, the sector has been plagued by recurring administrative and financial shortcomings, including allegations of corruption and mismanagement, as documented in media reports and academic studies, with instances of significant financial waste. The continued imposition of electricity tariffs that are disproportionate to the level of service and the actual hours of supply has placed an undue financial burden on consumers, driving many to rely on private alternative energy sources. This study aims to examine the legislative gaps and shortcomings in applying good governance principles within Lebanon’s electricity sector, in light of the ongoing financial collapse and administrative and financial irregularities at the Lebanese Electricity Corporation. It further investigates the legal implications of these deficiencies on the management of this public utility and the protection of consumer rights.